First occurrence of tetrodotoxins in bivalve mollusks from Northern Adriatic Sea (Italy). (February 2021) - Bordin, Paola; Dall'Ara, Sonia; Tartaglione, Luciana; Antonelli, Pietro; Calfapietra, Anna; Varriale, Fabio; Guiatti, Denis; Milandri, Anna; Dell'Aversano, Carmela; Arcangeli, Giuseppe; Barco, Lisa
Abstract: Tetrodotoxins are a potent neurotoxic class of toxins with potentially fatal effects if ingested by humans, and thus, these toxins are a dangerous threat for food safety. Tetrodotoxins are widely distributed among various organisms of different taxa, i.e. pufferfish, blue-ringed octopuses and marine gastropods. Lately the presence of these toxins has been reported in mussels ( Mytilus sp.). Countries like the United Kingdom, Greece, the Netherlands, and Italy have increasingly notified the detection of tetrodotoxins in these bivalves, which are widely diffused in European shellfish farming. In this context we report, for the first time, the detection of substantial amounts of tetrodotoxins in Mytilus galloprovincialis collected in Italy in a single area of the Northern Adriatic Sea (Marano Lagoon). Tetrodotoxin-positive mussels were identified in samples collected from that geographic area at the end of May in the context of official monitoring programs both in 2017 and 2018. After the positive results were obtained by means of mouse bioassay screening, tetrodotoxins were detected and quantified by HILIC-MS/MS, revealing the bioaccumulation in the mussels of 541 and 216 μg/kg in 2017 and 2018 respectively, the highest amount ever found in mollusks in Europe. The presence of tetrodotoxins at the concentration of 413 μg/kg was further confirmed with Liquid Chromatography coupled to High Resolution Mass Spectrometry in the mussels sampled in 2017. Highlights: Tetrodotoxins are neurotoxic and potentially fatal for humans Tetrodotoxins were found in shellfishes collected in Northern Adriatic sea The positive samples were from the same sampling point both in 2017 and 2018 The tetrodotoxin amount for one sample of 2017 was the highest recovered in Europe